ChemInform Abstract: Direct Synthesis of β‐Ketophosphonates and Vinyl Phosphonates from Alkenes or Alkynes Catalyzed by CuNPs/ZnO. Issue 52 (10th December 2015) - Gutierrez, Victoria; Mascaro, Evangelina; Alonso, Francisco; Moglie, Yanina; Radivoy, Gabriel
Abstract: It is found that alkynes conjugated with an aromatic ring or a carbon‐carbon double bond afford β‐ketophosponates as main products, whereas aliphatic alkynes or alkynes conjugated with a carbonyl group afford the corresponding vinyl phosphonates as mixtures of E/Z‐isomers.